2020
DOI: 10.1177/2324709620950107
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus Versus Novel Coronavirus-Induced Hemophagocytic Lymphohistocytosis: The Uncharted Waters

Abstract: Hemophagocytic lymphohistocytosis (HLH) is a hyperinflammatory syndrome characterized by fever, hepatosplenomegaly, and pancytopenia. It may be associated with genetic mutations or viral/bacterial infections, most commonly Epstein-Barr virus (EBV) and cytomegalovirus. As for the novel coronavirus, severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), also known as COVID-19 (coronavirus disease-2019), the cytokine storm it triggers can theoretically lead to syndromes similar to HLH. In this article, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…In this paper, we compared the clinical features of EBVinfected and non-infected children and found differences in the first symptoms, karyotype, immunophenotyping, clinical risk, secondary infection during chemotherapy, and lymphocyte subsets, suggesting that EBV infection is associated with these clinical features. More than half of primary EBV infections occur in children under 5 years old, such children present only with respiratory infections or infectious mononucleosis, and EBV infection is associated with hepatosplenomegaly in children (18,19). The results of this paper showed that the highest percentage of first symptoms were hepatosplenic lymph node enlargement in infected patients compared to non-EBV infected children, which further supports the conclusion that EBV infection can cause hepatosplenomegaly and is consistent with the characteristics of this virus.…”
Section: Discussionsupporting
confidence: 83%
“…In this paper, we compared the clinical features of EBVinfected and non-infected children and found differences in the first symptoms, karyotype, immunophenotyping, clinical risk, secondary infection during chemotherapy, and lymphocyte subsets, suggesting that EBV infection is associated with these clinical features. More than half of primary EBV infections occur in children under 5 years old, such children present only with respiratory infections or infectious mononucleosis, and EBV infection is associated with hepatosplenomegaly in children (18,19). The results of this paper showed that the highest percentage of first symptoms were hepatosplenic lymph node enlargement in infected patients compared to non-EBV infected children, which further supports the conclusion that EBV infection can cause hepatosplenomegaly and is consistent with the characteristics of this virus.…”
Section: Discussionsupporting
confidence: 83%
“…As the number of cases of this virus increases, so do the number of complications exposed. Chronic B-lymphocyte depletion ultimately puts patients at higher risk for infections other than SARS-CoV-2 [ 14 ]. EBV reactivation was closely related to the prognosis of patients with COVID-19, which may exacerbate COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…serum ferritin) in our patient triggered an initiation of a modified, etoposide-free treatment protocol with dexamethasone and rituximab. Although rituximab is generally accepted for treatment of EBV-HLH, its safety in active COVID-19 has not been established, with only one (non-transplant) case report published to date [ 18 ]. Mehta et al speculated that whilst rituximab might be risky at the beginning of SARS-CoV-2 infection by interfering with development of protective antibodies and viral clearance as recently showed by Avouvac et al [ 19 ], it might prove beneficial later (when seropositive) by reducing COVID-19-associated (HLH-like) hyper-inflammation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%